ChemInform Abstract: Synthesis of High Surface Area Mixed Metal Oxide from the NiMgAl LDH Precursor for Nitro‐Aldol Condensation Reaction. Issue 22 (15th May 2015) - Bharali, Dipshikha; Devi, Rasna; Bharali, Pankaj; Deka, Ramesh C.
Abstract: Title catalysts are synthesized and shown to have high catalytic activity towards nitro‐aldol condensation reaction.